Observations of alanine aminotransferase and aspartate aminotransferase in THRIVE studies treated orally with ximelagatran - Harenberg, Job; Jörg, Ingrid; Weiß, Christel (International journal of toxicology, 2006)
Treatment of acute venous thromboembolism (VTE) and prophylaxis of recurrent events has been investigated in the THRIVE (THRombin Inhibitor in Venous ThrombeEmbolism) Treatment and the THRIVE III trial using the oral direct thrombin inhibitor ximelagatran. Alanine aminotransferase (ALAT) increased in 9.6% and 6.4% of patients in the THRIVE Treatment and THRIVE III trials, respectively. The authors analysed the time course of the ALAT and in additionally of aspartate aminotransferase (ASAT) in blood from 52 and 23 patients participating in the THRIVE Treatment and the THRIVE III trials in Germany. Analysis of variance for repeated measures and t test were performed. In the THRIVE Treatment trial, ALAT was significantly higher at week 2 for enoxaparin/warfarin (p = .0039, t test) and at months 3 and 6 for ximelagatran (p = .0453, p = .0014, respectively). ASAT and ASAT/ALAT ratio values did not increase and not differ for both groups. In the THRIVE III trial, ALAT and ASAT did not increase and did not differ compared to the comparator placebo. 2 × 36 mg Ximelagatran, induced higher ALAT values at months 3 and 6 compared to 2 × 24 mg ximelagatran (p = .0105, p = .0063, respectively). ASAT did not differ between the two doses of ximelagatran. The ASAT/ALAT ratios were lower at week 2 for enoxaparin/warfarin (t-test, p = .0032) and at month 3 and 6 for 2 × 36 mg versus warfarin or 2 × 24 mg Ximelagatran (p between .0187 and .0002). The authors conclude that ALAT increases dose dependently during therapy with ximelagatran. The less frequent and lower increase of ASAT values compared to ALAT values indicates a nontoxic effect of ximelagatran on liver cells.